Coccidioidomycosis Involving the Cranium: A Case Report and Review of Current Literature - J. Antony, Suresh; S. Parikh, Monisha; Friedman, Glen (Infectious Disorders - Drug Targets, 2015)
We report a case of Coccidioidomycosis of the cranium that presented as a cystlike structure with adjoining bone destruction in a 40-year-old patient with underlying rheumatoid arthritis that was treated with a combination of lipid amphotericin B and longterm fluconazole. We also discuss the common risk factors and presentations of this unusual extra-pulmonary form of Coccidioidomycosis.
Keywords: osteomyelitis